Comparison of shear bond strengths of different types of denture teeth to different denture base resins - Prpić, Vladimir (J Adv Prosthodont, 2020)
PURPOSE: To determine the shear bond strengths of different denture base resins to different types of prefabricated teeth (acrylic, nanohybrid composite, and cross-linked) and denture teeth produced by computer-aided design/computer-aided manufacturing (CAD/CAM) technology. MATERIALS AND METHODS: Prefabricated teeth and CAD/CAM (milled) denture teeth were divided into 10 groups and bonded to different denture base materials. Groups 1–3 comprised of different types of prefabricated teeth and cold-polymerized denture base resin; groups 4–6 comprised of different types of prefabricated teeth and heat-polymerized denture base resin; groups 7–9 comprised of different types of prefabricated teeth and CAD/CAM (milled) denture base resin; and group 10 comprised of milled denture teeth produced by CAD/CAM technology and CAD/CAM (milled) denture base resin. A universal testing machine was used to evaluate the shear bond strength for all specimens. One-way ANOVA and Tukey post-hoc test were used for analyzing the data (α=.05). RESULTS: The shear bond strengths of different groups ranged from 3.37 ± 2.14 MPa to 18.10 ± 2.68 MPa. Statistical analysis showed significant differences among the tested groups (P<.0001). Among different polymerization methods, the lowest values were determined in cold-polymerized resin.There was no significant difference between the shear bond strength values of heat-polymerized and CAD/CAM (milled) denture base resins. CONCLUSION: Different combinations of materials for removable denture base and denture teeth can affect their bond strength. Cold-polymerized resin should be avoided for attaching prefabricated teeth to a denture base. CAD/CAM (milled) and heat-polymerized denture base resins bonded to different types of prefabricated teeth show similar shear bond strength values.